2014
DOI: 10.1186/s13023-014-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Holt Oram syndrome: a registry-based study in Europe

Abstract: BackgroundHolt-Oram syndrome (HOS) is an autosomal dominant disorder characterised by upper limb anomalies and congenital heart defects. We present epidemiological and clinical aspects of HOS patients using data from EUROCAT (European Surveillance of Congenital Anomalies) registries.MethodsThe study was based on data collected during 1990–2011 by 34 registries. The registries are population-based and use multiple sources of information to collect data on all types of birth using standardized definitions, metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 35 publications
3
59
0
5
Order By: Relevance
“…The difference between our results and those of Newbury-Ecob et al may reflect the fact that our cohort was from hand surgery clinics, whereas their patients came from cardiology and genetics clinics and an upper limb support group. We also found a higher incidence of thumb-index syndactyly compared with the previous reports, 19% vs 5%–11% 1,4 . Newbury-Ecob et al reported 64% of patients had forearm involvement, but details were not provided, and radioulnar synostosis was not mentioned (although limited forearm supination was noted).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The difference between our results and those of Newbury-Ecob et al may reflect the fact that our cohort was from hand surgery clinics, whereas their patients came from cardiology and genetics clinics and an upper limb support group. We also found a higher incidence of thumb-index syndactyly compared with the previous reports, 19% vs 5%–11% 1,4 . Newbury-Ecob et al reported 64% of patients had forearm involvement, but details were not provided, and radioulnar synostosis was not mentioned (although limited forearm supination was noted).…”
Section: Discussionsupporting
confidence: 65%
“…Barisic et al reported involvement of all thumbs in 73 HOS patients 1 , and Newbury-Ecob et al 5 reported 84% of 55 patients with HOS had thumb involvement. We found an intermediate incidence of 95%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations